2019
DOI: 10.1146/annurev-pharmtox-010818-021842
|View full text |Cite
|
Sign up to set email alerts
|

Novel Clinical Toxicology and Pharmacology of Organophosphorus Insecticide Self-Poisoning

Abstract: Organophosphorus insecticide self-poisoning is a major global health problem, killing over 100,000 people annually. It is a complex multi-organ condition, involving the inhibition of cholinesterases, and perhaps other enzymes, and the effects of large doses of ingested solvents. Variability between organophosphorus insecticides-in lipophilicity, speed of activation, speed and potency of acetylcholinesterase inhibition, and in the chemical groups attached to the phosphorus-results in variable speed of poisoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 118 publications
(140 reference statements)
1
84
0
1
Order By: Relevance
“…AChE acetyl cholinesterase, CNS central nervous system, ICU intensive care unit, OPs organophosphates failure and hypoxemia due to muscarinic effects on the cardiovascular and pulmonary systems (i.e., bronchospasm, aspiration, bradycardia, or hypotension), nicotinic effects on skeletal muscles (weakness and paralysis), loss of central respiratory drive, and seizures (rare). Initial treatment for acute MAL toxicity is mainly concerned with ensuring an adequate airway, oxygenation, and ventilation and stabilizing patient hemodynamics by reversing excessive muscarinic effects, mainly by using atropine (Eddleston et al 2008;Eddleston 2019). Once the patient is stable, the administration of an AChE-reactivating drug, such as pralidoxime or obidoxime, should be considered along with skin and/or gastric decontamination (Roberts and Aaron 2007) (Fig.…”
Section: Classical Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…AChE acetyl cholinesterase, CNS central nervous system, ICU intensive care unit, OPs organophosphates failure and hypoxemia due to muscarinic effects on the cardiovascular and pulmonary systems (i.e., bronchospasm, aspiration, bradycardia, or hypotension), nicotinic effects on skeletal muscles (weakness and paralysis), loss of central respiratory drive, and seizures (rare). Initial treatment for acute MAL toxicity is mainly concerned with ensuring an adequate airway, oxygenation, and ventilation and stabilizing patient hemodynamics by reversing excessive muscarinic effects, mainly by using atropine (Eddleston et al 2008;Eddleston 2019). Once the patient is stable, the administration of an AChE-reactivating drug, such as pralidoxime or obidoxime, should be considered along with skin and/or gastric decontamination (Roberts and Aaron 2007) (Fig.…”
Section: Classical Measuresmentioning
confidence: 99%
“…Both preclinical and clinical data suggest that they might be promising adjunct treatments. However, the evidence is currently insufficient to recommend their use, and the precise mechanism of how they might work remains unclear (Brvar et al 2018;Eddleston 2019). Mohammadi et al found that magnetic isotopes of magnesium significantly recovered MAL-induced arrhythmia and cardiac failure in rats (Mohammadi et al 2011).…”
Section: Novel Treatments For Mal Poisoningmentioning
confidence: 99%
“…According to the EMA (European Medical Agency) (2003), treating respiratory failure by controlled ventilation after intubation is the immediate therapeutic priority after poisoning by acute doses of organophosphate compounds (OP) (Stone, 2018a). OP and carbamates contribute to pesticide exposure with around 100,000 deaths/year worldwide (Eddleston, 2019). OP chemical warfare nerve agents, such as sarin, have intoxicated people during the Iran-Iraq war (midd-1980) (Stone, 2018a), and in Syria (2013Syria ( , 2017 (Dolgin, 2013).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Other organophosphate derivatives such as azinphos, chlorpyrifos, and diazinon are used for pest control on food and commodity crops worldwide (Sidhu et al, 2019). Persistence in the environment after agricultural use is limited, but more than 100,000 deaths per year result from organophosphate poisoning, mostly from self‐ingestion (Eddleston, 2019). Paraoxon and parathion also have pesticidal activity and are commonly used as model compounds for chemical warfare agents.…”
Section: Introductionmentioning
confidence: 99%